A Study On labour Welfare Measures of Kitex Limited, Kizhakkambalam - S. Gopalakrishnan AND MANSAR .K.H
The basic purpose of labor welfare is to enrich the life of employees and keep them happy and contented. Welfare facilities enable workers to have a richer and more satisfying life. It raises the standard of living of workers by indirectly reducing the burden on their pocket. Welfare means improving, faring or doing well. It is a comprehensive term, and refers to the physical, mental, moral and emotional wellbeing of an individual. Further the term welfare is a relative concept, relative in time and space. It therefore, varies from time to time, region to region and from country to country. Labor welfare is an important aspect in every organization with some added incentives which enable the workers to lead a decent life. There are several agencies involved in the labor welfare work namely the central government, employer’s trade union and other social service organization.